Kindergarten of the Air: From Australia to the world. (1st October 2019) - Griffen-Foley, Bridget
This article considers the radio programme for kindergarten-aged children that the Australian Broadcasting Commission (ABC) launched during the Second World War and continued to broadcast until 1985. Kindergarten of the Air, thought to be the 'first of its kind in the world', was to inspire interest from, and similar programmes throughout, the British empire and beyond. The article examines the imperial and international broadcasting networks that enabled the exchange of ideas and initiatives within the field of educational broadcasting, and the export of one of Australia's most successful radio initiatives, while also considering the willingness of the British Broadcasting Corporation (BBC) to be influenced by a dominion broadcaster.